Partial-mouth periodontal examination in post-orthodontic subjects - Staples Glenn; Freer Terrence J.; Basford Kaye (Sciendo, 1988)
A partial-mouth recording system for periodontal disease was applied to an untreated control group and a post-orthodontic study group. The results for the two groups were substantially different.